2013
DOI: 10.4103/2153-3539.106682
|View full text |Cite
|
Sign up to set email alerts
|

The successful implementation of a licensed data management interface between a Sunquest® laboratory information system and an AB SCIEXTM mass spectrometer

Abstract: Background:Interfacing complex laboratory equipment to laboratory information systems (LIS) has become a more commonly encountered problem in clinical laboratories, especially for instruments that do not have an interface provided by the vendor. Liquid chromatography-tandem mass spectrometry is a great example of such complex equipment, and has become a frequent addition to clinical laboratories. As the testing volume on such instruments can be significant, manual data entry will also be considerable and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The set of textural features extracted from a window of size 30 × 30 pixels around the bounding box of each candidate mitosis are as follows: 32 Phase Gradient (PG) features (16 orientations, 2 scales),[7] 1 roughness feature, 1 entropy feature. From each of these 34 features, 4 representative features were computed: (1) mean, (2) standard deviation, (3) skewness, (4) kurtosis.…”
Section: Resultsmentioning
confidence: 99%
“…The set of textural features extracted from a window of size 30 × 30 pixels around the bounding box of each candidate mitosis are as follows: 32 Phase Gradient (PG) features (16 orientations, 2 scales),[7] 1 roughness feature, 1 entropy feature. From each of these 34 features, 4 representative features were computed: (1) mean, (2) standard deviation, (3) skewness, (4) kurtosis.…”
Section: Resultsmentioning
confidence: 99%
“…The studies are summarized in Table 1. In this section, methods proposed for segmenting DRAs,[31323334] epithelial nuclei,[5151617181935] lymphocyte cells,[71320] tubule,[2122232425] and mitotic figures[682627282930] are discussed.…”
Section: Classification Of the Reviewed Studiesmentioning
confidence: 99%
“…Therefore, in a study by Mercan et al .,[32] a texton-based approach was proposed to distinguish between DRAs and irrelevant patches. In another study by Khan et al .,[31] Gabor-based texture features were used to differentiate hypocellular from hypercellular stroma. Gabor filters are extensively used in image analysis as they resemble the human visual system.…”
Section: Classification Of the Reviewed Studiesmentioning
confidence: 99%
“…Unfortunately, interfacing each of these peripheral instruments with the LIS is not always pursued or is deemed too resource intensive, because these interfaces may need to be built and maintained by in-house support teams, but the lack of an instrument-LIS interface can result in inefficient and error-prone daily workflow in the laboratory. It has been demonstrated that manual entry of microbiology results is a source of laboratory errors (47,48), and other clinical laboratories have demonstrated that the development of in-house interfaces between instruments and the LIS can be useful in reducing manual entry errors and hands-on time (49,50). In order to optimize the efficiency and accuracy of all instrument testing, interfaces between laboratory instruments and the LIS should be employed for data transfer whenever possible.…”
Section: Instrument Interfaces With the Lismentioning
confidence: 99%